Iowa Birdline update, September 13, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for September 13, 1993. Highlights include the continued presence of a Reddish Egret. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed